2017
DOI: 10.1038/ncomms14447
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporally restricted arenavirus replication induces immune surveillance and type I interferon-dependent tumour regression

Abstract: Immune-mediated effector molecules can limit cancer growth, but lack of sustained immune activation in the tumour microenvironment restricts antitumour immunity. New therapeutic approaches that induce a strong and prolonged immune activation would represent a major immunotherapeutic advance. Here we show that the arenaviruses lymphocytic choriomeningitis virus (LCMV) and the clinically used Junin virus vaccine (Candid#1) preferentially replicate in tumour cells in a variety of murine and human cancer models. V… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 65 publications
2
35
0
Order By: Relevance
“…Therefore, we reasoned that revealed that accumulation and activation of intratumoral CD8 + T effector cells was enhanced by LCMV infection, suggesting that the limited infiltration of CD8 + T cells observed in B16F10-OVA melanoma recovered by LCMV. We have previously shown that LCMV can replicate in many tumor models [9], which strongly support that LCMV and Junín virus vaccine, Candid#1 reversed the MHC class I expression. We discovered that LCMV treatment promoted the proliferation of CD8 + T cells in draining LNs, and LCMV combined PD-1 cocktail significantly reduced tumor growth compared to LCMV treatment alone (data not show).…”
Section: Furthermore Replicating Non-oncolytic Arenaviruses Like Lcmsupporting
confidence: 57%
See 3 more Smart Citations
“…Therefore, we reasoned that revealed that accumulation and activation of intratumoral CD8 + T effector cells was enhanced by LCMV infection, suggesting that the limited infiltration of CD8 + T cells observed in B16F10-OVA melanoma recovered by LCMV. We have previously shown that LCMV can replicate in many tumor models [9], which strongly support that LCMV and Junín virus vaccine, Candid#1 reversed the MHC class I expression. We discovered that LCMV treatment promoted the proliferation of CD8 + T cells in draining LNs, and LCMV combined PD-1 cocktail significantly reduced tumor growth compared to LCMV treatment alone (data not show).…”
Section: Furthermore Replicating Non-oncolytic Arenaviruses Like Lcmsupporting
confidence: 57%
“…Type I and type II interferon signaling contribute to the upregulation of MHC-I on tumor cells [28,[48][49][50]. In our previous studies [9] we showed that replicating arenaviruses induce a strong interferon response via the activation of the innate immune response. Therefore, we reasoned that revealed that accumulation and activation of intratumoral CD8 + T effector cells was enhanced by LCMV infection, suggesting that the limited infiltration of CD8 + T cells observed in B16F10-OVA melanoma recovered by LCMV.…”
Section: Furthermore Replicating Non-oncolytic Arenaviruses Like Lcmmentioning
confidence: 93%
See 2 more Smart Citations
“…The mechanism of virotherapy is not yet fully understood, but it can be broadly divided into the recruitment and activation of immune cells by inflammatory cytokines and the direct lysis of tumor cells. According to a published study (47), nononcolytic LCMV showed superior anticancer effects compared with the oncolytic vesicular stomatitis virus widely used in virotherapy. Kalkavan and colleagues found that locally or systemically administered LCMV preferentially replicated in cancer cells, causing Ly6C þ monocytes to secrete type I IFNs, resulting in the activation of tumorspecific CD8 þ T cells and tumor regression (47).…”
Section: Discussionmentioning
confidence: 99%